1979
DOI: 10.1007/bf01963302
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of a heat-resistant exotoxin produced byMacrophomina phaseolina (Tassi) Goid in culture

Abstract: A partially purified preparation of a water-soluble, heat-resistant, nonspecific exotoxin produced by a strain of Macrophomina phaseolina, isolated from Phaseolus mungo L. could reduce Cu++ ions and produced a red colour with 2,4-dinitrophenyl hydrazine reagent. It caused inhibition of seed germination, wilting of cult seedlings, stunted growth of young seedlings and loss of permeability of the cell membrane. Seedlings of P. mungo, grown in presence of the toxin showed a slight increase in the contents of prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…phaseolina has been reported to produce several mycotoxins that are candidates for toxin-mediated initiation of infection by generating a necrotic zone. These mycotoxins include phaseolinone [25], botryodiplodin [26], and patulin, because the M. phaseolina genome contains genes for its biosynthetic enzymes [27]. Siddiqui et al (1979) [25] identified phaseolinone in culture extracts of pathogenic M. phaseolina isolated as an endophyte of mung bean.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…phaseolina has been reported to produce several mycotoxins that are candidates for toxin-mediated initiation of infection by generating a necrotic zone. These mycotoxins include phaseolinone [25], botryodiplodin [26], and patulin, because the M. phaseolina genome contains genes for its biosynthetic enzymes [27]. Siddiqui et al (1979) [25] identified phaseolinone in culture extracts of pathogenic M. phaseolina isolated as an endophyte of mung bean.…”
Section: Introductionmentioning
confidence: 99%
“…These mycotoxins include phaseolinone [25], botryodiplodin [26], and patulin, because the M. phaseolina genome contains genes for its biosynthetic enzymes [27]. Siddiqui et al (1979) [25] identified phaseolinone in culture extracts of pathogenic M. phaseolina isolated as an endophyte of mung bean. Dhar et al (1982) [28] proposed the structure of the isolated toxin to be an epoxidized analog of a known phytotoxin, phomenone, which is part of an extensive family of phytotoxic eremophilane sesquiterpenoid (C-15) toxins produced by numerous plant pathogenic fungi [29].…”
Section: Introductionmentioning
confidence: 99%
“…Charcoal rot is caused by the fungus Macrophomina phaseolina (Tassi) Goid which infects plant roots from the soil by a toxin-mediated mechanism. Macrophomina phaseolina secretes two toxins (Figure 2), phaseolinone [15] [16] and (-)-botryodiplodin [17]. Although the mechanisms of charcoal rot infection via toxins are not well understood, infection of crop through the roots is [67].…”
Section: Introductionmentioning
confidence: 99%
“…The fungus Macrophomina phaseolina (Tassi) Goid, a widely distributed plant pathogen, causes inhibition of seed germination, wilting of seedlings and root rot in several agriculturally important crop plants (Butler and Bisby 1960;Bilgrami et al 1979;Siddiqui et al 1979). Phaseolinone ( Fig.…”
Section: Introductionmentioning
confidence: 99%